VD_FINDINFO HC / 2011 / 295 vom 12. Mai 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH), 310 CPC (CH), 317 al. 1 CPC (CH)